Accurately predicting hit songs using neurophysiology and machine learning - Merritt, Sean H.; Gaffuri, Kevin; Zak, Paul J. (Frontiers in Artificial Intelligence, 2023)
Identifying hit songs is notoriously difficult. Traditionally, song elements have been measured from large databases to identify the lyrical aspects of hits. We took a different methodological approach, measuring neurophysiologic responses to a set of songs provided by a streaming music service that identified hits and flops. We compared several statistical approaches to examine the predictive accuracy of each technique. A linear statistical model using two neural measures identified hits with 69% accuracy. Then, we created a synthetic set data and applied ensemble machine learning to capture inherent nonlinearities in neural data. This model classified hit songs with 97% accuracy. Applying machine learning to the neural response to first minute of songs accurately classified hits 82% of the time showing that the brain rapidly identifies hit music. Our results demonstrate that applying machine learning to neural data can substantially increase classification accuracy for difficult to predict market outcomes.